Identifikasi sumber pencemar Nitrogen (n) dan Fosfor (p) pada pertumbuhan melimpah tumbuhan air di Danau Tempe, Sulawesi Selatan - Syamsul Bahri (JURNAL SUMBER DAYA AIR, 2016)
Tempe Lake is one of 15 lakes as national priority to be saved. Today, the Tempe Lake has been blooming of aquatic weeds. The aims of research are i). to know the vegetation succesion, ii). To know the condition of water quality in lake and input river to lake, iii). To identify the main pollution sources of the nitrogen (N) and fosfor (P). The research carried out in dry season on June and August 2015. Analysis of succesion vegetation using the theory of vegetation succession in shallow lakes. Analysis of water quality using the criteria for fisheries and trophic status. Identification of N and P pollutant sources using secondary data namely agriculture area, type of fertilizer, total population, livestock. Based on the research, that in Tempe Lake has been processing the succession of vegetation, at least about four group of vegetation dominantly, namely phytoplankton, floating plant, emergent plant, and fringing plant. The lake water quality and the input river to lake still meets the criteria for fisheries. However, according to the status trophic of lake based on N dan P were hypertrophic with the average concentration N-total 0,697 mg/L and P-total 0,224 mg/L. The status trophic for the input river to lake based on N was oligotrophic with the average concentration of N-total 0,362 mg/L and based on P was eutrophic with the average concentration of P-total 0,291 mg/L.